On the occurence of Bullations in the Seagrass, Halophila Ovalis (R. Brown) Hooker F. From Bais Bay, Central Philippines - Meñez, Ernani G.; Calumpong, Hilconida P. (Silliman Journal, 2023)
In a survey of seagrasses in Bais Bay, Negros Oriental in Central Visayas, Philippines in April 1984 and June 1985, the authors collected an "unusual" looking seagrass in the intertidal area. Material collected in both years were sterile. When examined closely, more than half of the larger leaves were found to have "bullations". These bullations are due to the presence of bulliform cells described by Esau (1965) as "enlarged epidermal cells with their anticlinal walls ... participating in involution and folding movements". In grass leaves, these bulliform cells enable the leaves to fold or roll during excessive loss of water (Esau, 1965), as in intertidal areas.